O Supremo Tribunal Federal e seu poder contramajoritário sobre as medidas provisórias / The Federal Supreme Court and its counter-majoritarian power over the Provisional Measures - Silveira, Daniel Barile da (Revista Direito e Práxis, 2016)
DOI: 10.12957/dep.2016.17018 Resumo O presente artigo busca estudar o comportamento judicial do Supremo Tribunal Federal no julgamento das ações diretas de inconstitucionalidade (ADIs) em face das medidas provisórias, durante o período de 1988-2011. Neste sentido, a intenção é de diagnosticar qual o poder de veto que o STF se utiliza para barrar ou não estas políticas, exercitando sua função de "accountability" horizontal na separação de poderes. Palavras-chaves: Supremo Tribunal Federal; poder de veto; medidas provisórias. Abstract This article aims to study the legal behavior of the Brazilian Supreme Court in the trial of the Direct Unconstitutionality Action (ADIs) on the provisory measures during the period 1988-2011. In this sense, the intention of this work is diagnosticate what is the veto power that the Supreme Court uses to prevent or not prevent that policies, practicing its accountability function on the separation of the powers. Independence, political relations and judicial practice of tripartite powers: an analysis of the judgment in the Supreme Court of Direct Unconstitutionality Actions on the power of presidential decree (Provisory Measures). Keywords: Supreme Court; veto power; provisional measures.